Islamic Inheritance Law Policies Viewed from The Perspective of Gender Justice according to Applicable Regulations in Indonesia - Salwa Billa Mirza Ridwan (Proceeding International Conference Restructuring and Transforming Law, 2024)
As a country where the majority of the population is Muslim, it is possible that many members of the community use the Islamic legal system. But along with the times characterized by progress and technology, the principles of Islamic law continue to progress rapidly and always follow the changing times for the benefit of people in the world. Without distinguishing between men and women. In Indonesian legal literature, the word "inheritance" is often used. The word comes from Arabic but in practice it is more commonly called "Heritage". The verb form is Warastra Yasiru and the masdar word is Miras. There are three other masdar according to the science of sasaf, namely wirsan, wirasatan and irsan. While the word inheritance is a person who gets inheritance or heirloom. From the description of the discussion above, it can be concluded that Islamic Inheritance Law has accommodated the principle of gender justice law.